Two steps forward - Cohn, Rachel (Simon & Schuster Books for Young Readers, 2006)
Fourteen-year-old Annabel's extended family gathers in Los Angeles for several weeks over the summer where she must contend with step- and half-sisters and brothers, and her own mother's failing marriage.